Responsibility of international organizations : essays in memory of Sir Ian Brownlie - Brownlie, Ian; Ragazzi, Maurizio (2013)
In December 2011, the United Nations General Assembly adopted the International Law Commission's articles on the responsibility of international organizations, bringing to conclusion not only nearly ten years of reflection by the Commission, governments and organizations on this specific topic, but also decades of study of the wider subject of international responsibility, which had initially focused on State responsibility. Parallel to this reflection by the Commission, diplomats and public officials, the body of international case-law and literature on the many facets of the topic has steadily been growing. Responsibility of International Organizations: Essays in Memory of Sir Ian Brownlie contributes to the body of international literature by collecting a broad spectrum of different and sometimes differing perspectives from well-known experts in the field, ranging from the bench to the Commission, academia, and the world of in-house counsel. The book is also a memorial to the renowned Sir Ian Brownlie, himself a former Chairman of the International Law Commission who, as a leading scholar and practitioner, greatly contributed to the reflection on international responsibility, including the responsibility of international organizations. Edited by Maurizio Ragazzi, a former pupil of Sir Ian, the book is an ideal companion to International Responsibility Today , a collection of essays on international responsibility which the same editor presented in 2005 in memory of Oscar Schachter, and to which Sir Ian Brownlie had contributed. The essays collected in Responsibility of International Organizations: Essays in Memory of Sir Ian Brownlie , conveniently grouped by the editor under broad areas for the reader's benefit, will be relevant not only to all those interested in this specific subject but also, more generally, to all those engaged in the field of international law and the law of international organizations.
pt. 1. Setting the stage : international organizations' responsibility between codification and progressive development -- pt. 2. Assessing the commission's approach : state responsibility and responsibility of international organizations -- pt. 3. Particular perspectives : international organizations and other entities -- pt. 4. Special concerns : selected issues regarding the articles.
Includes bibliographical references (pages 453-465) and index.
Keywords: Tort liability of international agencies; Government liability (International law); LAW -- International; Government liability (International law); Tort liability of international agencies; Electronic books